Utilização de polissacarídeos para desenvolvimento de materiais avançados : nanowhiskers de quitina/quitosana e microesferas de amido - Pereira, Antonio Guilherme Basso (2013)
The study developed in this Thesis has two main focuses. In the first one, the preparation of chitin and chitosan nanowhiskers and their application in the preparation of electrospun nanofibers based on cellulose acetate were described. Pure chitin was isolated from crab shell chitin at 75 % yield and hydrolyzed (3 N HCl, 30 mL/g, 104 ºC) to chitin nanowhiskers (CtNWs) at 65 % yield with degree of acetylation (DA) of 81 % confirmed by FTIR. TEM analysis showed the CtNWs dimensions are 16 nm (width) and 214 nm (length) with aspect ratio of 13. CtNWs self-assemble during freezing drying into layers containing sub-micron structures. Chitosan nanowhiskers (CsNWs) were derived from deacetylation of CtNWs under alkaline treatment. A systematic study on CtNWs condition (suspension or freeze-dried), temperature and reaction time on deacetylation and on yield of final product was performed. FTIR revealed that DA of CsNWs was ca. 60 % independent on reaction time. It was shown the deacetylation occurs preferentially at the surface of CtNWs and the extension of reaction increases with increasing of reaction time, as evidenced by the increase of positive charges in zeta potential measurements, associated to loss of crystallinity from 86 % (CtNWs) to ca. 50 % (CsNWs) and reduction of yield. However, the rod-shape morphology was maintained. TGA and DSC data showed only slightly variations between CtNWs and CsNWs corroborating to zeta potential and FTIR data which suggest surface deacetylation. Furthermore, it was possible to follow the deacetylation reaction through 1H NMR e 13C NMR spectroscopy. The 1H NMR spectra presented good resolution considering the fact that the samples are nanocrystals (solids). Nanocomposites electrospun nanofibers based on cellulose acetate and chitin nanowhiskers (CtNWs) were prepared by electrospinning (14 kV, 1 mL/h, distance of 25 cm, concentration of 15 %) a suspension prepared in ternary solvent system: Acetone/DAMAc/H2O (61.7/33.3/5 %-v/v/v). The addition of CtNWs at 2.5 % induced a decrease in the average diameter of fibers from 563 nm (control) to 240 nm. It was also showed that the surface properties of electrospun nanofibers could be tuned by the electrostatic adsorption of CsNWs. Biological assays showed the nanofibers based on pure CA, or those containing CtNWs or CsNWs promoted an increase in the VERO cell growth. Besides, the nanofibers with chitosan nanowhiskers adsorbed at the surface have antibacterial activity against Escherichia coli with 99 % of CFU death in 24 h. Similarly, CtNWs and CsNWs suspensions presented antibacterial activity, as well. For 24 h of contact the bacterial death was 85 % and 98 % for CtNWs and CsNWs, respectively. In the second focus of this Thesis, crosslinked microspheres based on starch, previously modified by the insertion o vinyl groups, were prepared to act as oral curcumin deliverer, drug that presents antitumor activity. The microspheres showed high loading efficiency (~90%) even in loading solution with different CUR concentrations. In vitro release assays data showed that the CUR release is governed by anomalous transport (n = 0.73, contribution of both diffusion and swelling) and pH-dependent. Cytotoxicity assays showed that starch-mod/MBA microspheres could improve the cytotoxicity of CUR towards Caco-2 and HCT-116 cell lines up to 40 times than that found for pure CUR. This behavior was attributed to the slowly and sustained release of CUR from the microspheres, avoiding premature degradation.